Intensity and performance related differences in propelling and mechanical efficiencies - Cappaert, J. M.; Bone, M.; Troup, J. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The purpose of the study was to determine propelling (PE) and mechanical efficiency (ME) of freestyle swimming under two conditions: (i) at velocities having high aerobic or anaerobic demand and (ii) during swims specific to sprint, middle distance and distance competitors. The results suggest that PE decreases as the anaerobic energy sources increase. Mechanical efficiency does not seem to be affected by the predominant energy source used.